Исследование смеси олигомерных силсесквиоксанов методами гельпроникающей хроматографии и матричной лазерно-активированной десорбционно/ионизационной масс-спектрометрии - Клименко, Н.С.; Гуменная, М.А.; Шевчук, А.В.; Бойчук, В.В.; Снегир, С.В.; Покровский, В.А.; Шевченко, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The mixture of oligosilsesquioxanes with tertiary amine and primary and secondary hydroxylic groups in the organic part of a molecule is investigated by gel penetrating chromatography (GPC) and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI ToF MS). These compounds are characterized by a polymodal molar mass distribution, as shown by GPC measurements. Due to a large number of polar hydroxylic groups, a very stable H-bond network is formed at room temperature. This network cannot be completely disrupted by dissolving in N,N-dimethylformamide as well as by the addition of LiCl and Cu(OAc)2 in the solution. This is a reason for a molar mass displacement to the side of higher values by GPC data. There is an essential discrepancy between GPC and MALDI ToF MS data.